Heparin Regulates ICAM-1 Expression in Human Endothelial Cells: An Example of Non-Cytokine-Mediated Endothelial Activation - Miller, Steven J.; Hoggatt, A. M.; Faulk, W. Page (Thrombosis and Haemostasis, 1998)
Activated endothelial cells up-regulate the expression of several molecules on their plasma membranes, including intercellular adhesion molecule-1 (ICAM-1). The role of heparin in regulating endothelial cell gene expression is unclear. We thus have investigated the ability of heparin to regulate ICAM-1 gene expression by using flow cytometry and the ribonuclease protection assay with human umbilical vein and aortic endothelial cells cultured in growth medium supplemented with 90 μg/ml heparin (heparin-sufficient, HS) or in growth medium without added heparin (heparin-deficient, HD). We found that HD medium increased plasma membrane protein and mRNA for ICAM-1 but not for HLA-DR, even though both ICAM-1 and HLA-DR protein and mRNA were inducible by gamma interferon (IFN-γ). In addition, phorbol ester and IFN-γ increased the expression of plasma membrane ICAM-1 or ICAM-1 and HLA-DR, respectively, more in HD medium than in HS medium. We found that the HD-mediated increase of ICAM-1 mRNA was reversible by the addition of heparin, and that the half-life of ICAM-1 mRNA was the same in both HS- and HD-treated cells. Also, heparin was found to suppress increases in ICAM-1 mRNA at a concentration as low as 5 μg/ml. These findings indicate that heparin deficiency induces endothelial activation characterized by increased ICAM-1, and that such induction is not dependent on cytokines or endotoxin. The modulation of ICAM-1 expression by heparin appears to occur at the transcriptional level. Thus, heparin may have a role in regulating endothelial function by affecting the expression of ICAM-1, thereby impacting upon the trans-endothelial trafficking of leukocytes.